E0472 Two-year clinical efficacy of sirolimus—versus paclitaxel—versus zotarolimus-eluting stents in diabetic patients. (17th November 2010) - Chen, Kang-Yin; Rha, Seung-Woon; Li, Yong-Jian; Li, Guang-Ping; Park, Ji-Young; Ramasamy, Sureshkumar; Poddar, Kanhaiya; Choi, Byoung Geol; Kim, Yun Kyung; Na, Jin Oh; Choi, Cheol Ung; Lim, Hong Euy; et al.
Abstract : Background: Drug-eluting stents (DESs) have drastically improved the angiographic and clinical outcomes of percutaneous coronary intervention (PCI) in patients (pts) with diabetes mellitus. However, little has been known whether the different types of DESs have similar efficacy in Asian diabetic pts. Methods: A total of 305 diabetic pts who underwent PCI with Sirolimus (SES group; Cypher, n=102 pts, 247 lesions), Paclitaxel (PES group; Taxus, n=138 pts, 414 lesions) or Zotarolimus (ZES group; Endeavour, n=65 pts, 138 lesions)-eluting stents were enrolled. Angiographic outcomes at 6 months and cumulative clinical outcomes up to 2 years were compared among these 3 groups. Results: These 3 groups had similar baseline clinical and procedural characteristics except that SES group had longer stent length and PES group had smaller stent diameter as compared with other groups. Six-month angiographic outcomes showed that SES group had less binary restenosis, lower restenosis percent, and late loss as compared with the other 2 groups. Major clinical outcomes were similar among the 3 groups up to 2 years except a trend towards lower incidence of TVR in SES group as compared with the other 2 groups. ZES group had 1 acute, 1 subacute, and 1 late stent thrombosis (ST), while the other 2 groups didn't have ST throughout the follow-up period (Table). Conclusions: Although SES had favourable angiographic outcomes at 6 months as compared with PES and ZES, these angiographic benefits were not translated into better clinical outcomes in patients with diabetes up to 2 years. Table: Six-month Angiographic and 2-year clinical outcomes Variable, n (%) SES Group (n=102 pts, 247 lesions) PES Group (n=138 pts, 414 lesions) ZES Group (n=65 pts, 138 lesions) p value Stent diameter, mm 2.95±0.36 2.86±0.38 3.03±0.44 <0.001 Stent length, mm 26.87±6.49 25.61±7.08 24.10±5.87 0.008 Binary restenosis 12 (7.5) 40 (15.9) 16 (19.8) 0.013 Restenosis percent, % 19.45±17.86 28.51±21.93 32.44±25.71 <0.001 Late loss, mm 0.45±0.49 0.85±1.72 0.73±0.69 0.008 Cardiac death 2 (2.0) 1 (0.7) 1 (1.5) 0.696 Q-wave MI 0 (0) 0 (0) 0 (0) 1.000 Non-Q-wave MI 0 (0) 0 (0) 0 (0) 1.000 TLR 6 (5.9) 16 (11.6) 9 (13.8) 0.190 TVR 8 (7.8) 22 (15.9) 12 (18.5) 0.092 TVR-MACE 13 (12.7) 25 (18.1) 15 (23.1) 0.218 Stent thrombosis 0 (0) 0 (0) 3 (4.6) 0.004.